An updated systematic review and meta-analysis of the efficacy of vitamin D food fortification - Black, Lucinda; Seamans, K.; Cashman, K.; Kiely, M. (American Society for Nutrition, 2012)
Food fortification is a potentially effective public health strategy to increase vitamin D intakes and circulating 25-hydroxyvitamin D [25(OH)D] concentrations. We updated a previous systematic review to evaluate current evidence from randomized controlled intervention studies in community-dwelling adults of the effect of fortified foods on 25(OH)D concentrations. Ovid MEDLINE, PubMed, CINAHL, Embase, and Cochrane Central Register of Controlled Trials were searched for randomized controlled intervention studies with vitamin D-fortified foods in free-living adults and data on circulating 25(OH)D. Two reviewers independently screened 441 papers for eligibility and extracted the relevant data. A meta-analysis of the absolute mean change in circulating 25(OH)D concentrations was conducted using a random effects model. Sixteen studies from 15 publications were included, of which 14 showed a significant effect of fortified foods on 25(OH)D concentrations. Heterogeneity was high (P = < 0.0001, I 2 = 89%) and was partly explained by dose, latitude (range, 3-608), and baseline 25(OH) D (range, 24.0-83.6 nmol/L). When combined in a random effects analysis (n = 1513; 767 treated, 746 controls), a mean individual intake of ~11 µg/d (440 IU/d) from fortified foods (range, 3-25 µg/d) increased 25(OH)D by 19.4 nmol/L (95% CI: 13.9, 24.9), corresponding to a 1.2 nmol/L (95% CI: 0.72, 1.68) increase in 25(OH)D for each 1 µg ingested. Vitamin D food fortification increases circulating 25(OH)D concentrations in community-dwelling adults. Safe and effective food-based strategies could increase 25(OH)D across the population distribution and prevent vitamin D deficiency with potential benefit for public health. © 2012 American Society for Nutrition.